2016
DOI: 10.1124/mol.116.107185
|View full text |Cite|
|
Sign up to set email alerts
|

G-Protein–Coupled Receptor Kinase 2 as a Potential Modulator of the Hallmarks of Cancer

Abstract: Malignant features-such as sustained proliferation, refractoriness to growth suppressors, resistance to cell death or aberrant motility, and metastasis-can be triggered by a variety of mutations and signaling adaptations. Signaling nodes can act as cancer-associated factors by cooperating with oncogene-governed pathways or participating in compensatory transduction networks to strengthen tumor properties. G-protein-coupled receptor kinase 2 (GRK2) is arising as one of such nodes. Via its complex network of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 85 publications
1
39
0
Order By: Relevance
“…GRK2 is emerging as an important "oncomodulator," a protein that influences multiple cellular functions related to the hallmarks of cancer, such as cell proliferation, cell survival, cell motility, cell metabolism, and angiogenesis, via its impact on cancer-relevant signaling networks (38). Many recent studies show recently been extended beyond B cell lymphoma to include T cell malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GRK2 is emerging as an important "oncomodulator," a protein that influences multiple cellular functions related to the hallmarks of cancer, such as cell proliferation, cell survival, cell motility, cell metabolism, and angiogenesis, via its impact on cancer-relevant signaling networks (38). Many recent studies show recently been extended beyond B cell lymphoma to include T cell malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…GRK2 has been reported to influence tumor progression in several different cancers, and the specific mechanism by which GRK2 exerts its influence depends on the tumor cell type. For example, it has been reported that GRK2 promotes the growth of certain breast cancers via phosphorylation and activation of histone deacetylase 6 (HDAC6) (38,75). As another example, 2 recent reports suggest that GRK2 is overexpressed in pancreatic cancer and may serve as an indicator of unfavorable prognosis (76,77).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRKs phosphorylate specific residues in the cytoplasmic domains of activated GPCRs, which is a critical step for the recruitment and binding of arrestins. GRKs modulate the responses to many GPCRs involved in tumor signaling and act as hubs regulating several cellular processes related to cancer progression through interactions with other components of the signal‐transduction cascades . Recent studies have shown that GRK6 deficiency promotes tumor metastasis through consequent up‐regulation of metastasis‐mediating matrix metalloproteinases (MMPs) …”
mentioning
confidence: 99%
“…GRKs modulate the responses to many GPCRs involved in tumor signaling and act as hubs regulating several cellular processes related to cancer progression through interactions with other components of the signal-transduction cascades. (26,27) Recent studies have shown that GRK6 deficiency promotes tumor metastasis through consequent up-regulation of metastasis-mediating matrix metalloproteinases (MMPs). (28) In the current study, we demonstrate that CD97 promotes HCC metastasis.…”
mentioning
confidence: 99%